2015
DOI: 10.5301/ejo.5000683
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Surgery with Melphalan Irrigation for Vitreous Hemorrhage in an Only Eye with Retinoblastoma

Abstract: Despite the high risk of intraocular surgery, the need to preserve the only potentially seeing eye with treated retinoblastoma may require PPV. Thus, in unclear cases of VH with suspected viable tumor, PPV with intraocular melphalan irrigation, with caution, may be a reasonable procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 7 publications
0
13
0
3
Order By: Relevance
“…If an intraocular procedure is preferred, tumor reactivation should be ruled out as the cause of the detachment. Pars plana vitrectomy (23 or 25G) with melphalan irrigation (5 μg/ml) with or without silicone oil tamponade is possible (Yarovoy et al, 2015). In the case of retinal detachment occurring concomitantly to proliferative vitreoretinopathy, with or without retinal dehiscence, an intravitreal anti-VEGF injection can be successfully given one week prior to vitrectomy under melphalan infusion combined with retinotomy (Stathopoulos et al, 2018a).…”
Section: Surgical Repairmentioning
confidence: 99%
“…If an intraocular procedure is preferred, tumor reactivation should be ruled out as the cause of the detachment. Pars plana vitrectomy (23 or 25G) with melphalan irrigation (5 μg/ml) with or without silicone oil tamponade is possible (Yarovoy et al, 2015). In the case of retinal detachment occurring concomitantly to proliferative vitreoretinopathy, with or without retinal dehiscence, an intravitreal anti-VEGF injection can be successfully given one week prior to vitrectomy under melphalan infusion combined with retinotomy (Stathopoulos et al, 2018a).…”
Section: Surgical Repairmentioning
confidence: 99%
“…With the rapid development of local chemotherapy treatments in recent years, this situation may come to an end. Several studies have reported on the combined use of IViC and PPV for advanced retinoblastoma in small sample cases [ 9 , 10 , 13 ]. Recently, Zhao et al reported on planned PPV with IViC in 21 cases of refractory retinoblastoma, with eye preservation achieved in 85.7% (18/21) of the cases with a median of 5.1 years of follow-up [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, endoresection by pars plana vitrectomy (PPV) is the ideal way to eradicate a tumour and solve vitreoretinal complications, but its use in the treatment of retinoblastoma has been controversial due to the high risk of metastasis, orbital seeding and extraocular extension [8]. However, the recent success of IViC has raised the possibility of surgical intervention again [9,10]. In this study, we attempted IViC-assisted endoresection in refractory monocular ICRB group D retinoblastoma patients.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of local chemotherapy treatments in recent years, this situation may come to an end. Several studies have reported on the combined use of IViC and PPV for advanced retinoblastoma in small sample cases (9,10,13) . Recently, Zhao et al reported on planned PPV with IViC in 21 cases of refractory retinoblastoma, with eye preservation achieved in 85.7%…”
Section: Discussionmentioning
confidence: 99%